Walidacja narzędzia diagnostycznego ,,Skale Inteligencji i Rozwoju dla Dzieci w Wieku Przedszkolnym (IDS-P)" z udziałem grupy dzieci z rozpoznanym płodowym zespołem alkoholowym wg kryteriów waszyngtońskich - Palicka, Iwona; Śmigiel, Robert (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Patients with FASD are still a diagnostic challenge for doctors and clinical psychologists due to the heterogeneity of symptoms connected with the structural and functional damages of brain. From the clinical point of view, an erroneous diagnosis leads to an incorrect treatment, an increased risk of secondary psychosocial disorders as well as a loss of a chance of an appropriate prevention. A basis of correct educational-therapeutic actions is a correct psychological diagnosis, which allows to extract developmental problems and to underline the cognitive resources. However, the psychologists lack an accurate and comprehensive tool to evaluate the cognitive functions of small children with FASD. The presented battery called: Intelligence and Development Scales for Pre-School Children IDS-P is a comprehensive research tool, sensitive to the cognitive difficulties of children with FASD.